Neutrophil extracellular traps: a role in inflammation and dysregulated hemostasis as well as in patients with COVID-19 and severe obstetric pathology - A. D. Makatsariya; E. V. Slukhanchuk; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; N. A. Makatsariya; S. V. Akinshina; A. S. Shkoda; L. L. Pankratyeva; G. C. Di Renzo; G. Rizzo; K. N. Grigorieva; et al. (IRBIS LLC, 2021)
Numerous studies have proven a close relationship between inflammatory diseases and the state of hypercoagulability. In fact, thromboembolic complications represent one of the main causes of disability and mortality in acute and chronic inflammatory diseases, cancer and obstetric complications. Despite this, the processes of hemostasis and immune responses have long been considered separately; currently, work is underway to identify the molecular basis for a relationship between such systems. It has been identified that various pro-inflammatory stimuli are capable of triggering a coagulation cascade, which in turn modulates inflammatory responses. Neutrophil extracellular traps (NETs) are the networks of histones of extracellular DNA generated by neutrophils in response to inflammatory stimuli. The hemostasis is activated against infection in order to minimize the spread of infection and, if possible, inactivate the infectious agent. Another molecular network is based on fibrin. Over the last 10 years, there has been accumulated a whole body of evidence that NETs and fibrin are able to form a united network within a thrombus, stabilizing each other. Similarities and molecular cross-reactions are also present in the processes of fibrinolysis and lysis of NETs. Both NETs and von Willebrand factor (vWF) are involved in thrombosis as well as inflammation. During the development of these conditions, a series of events occurs in the microvascular network, including endothelial activation, NETs formation, vWF secretion, adhesion, aggregation, and activation of blood cells. The activity of vWF multimers is regulated by the specific metalloproteinase ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13). Studies have shown that interactions between NETs and vWF can lead to arterial and venous thrombosis and inflammation. In addition, the contents released from activated neutrophils or NETs result in decreased ADAMTS-13 activity, which can occur in both thrombotic microangiopathies and acute ischemic stroke. Recently, NETs have been envisioned as a cause of endothelial damage and immunothrombosis in COVID-19. In addition, vWF and ADAMTS-13 levels predict COVID-19 mortality. In this review, we summarize the biological characteristics and interactions of NETs, vWF, and ADAMTS-13, the effect of NETs on hemostasis regulation and discuss their role in thrombotic conditions, sepsis, COVID-19, and obstetric complications.